2005
DOI: 10.1097/01.jcp.0000162800.64378.82
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Weight Gain and Olanzapine Plasma Concentrations

Abstract: Atypical antipsychotics, including olanzapine, have been associated with clinically significant weight gain in some patients. The purpose of this study was to determine if weight gain was associated with increasing plasma concentrations during olanzapine treatment in subjects with schizophrenia. This study included 39 acutely ill subjects with schizophrenia, schizoaffective disorder, or schizophreniform disorder (DSM-III-R or DSM-IV). Assessments included the Brief Psychiatric Rating Scale (BPRS), the Scale fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 15 publications
1
26
1
Order By: Relevance
“…For patients identified as most likely to experience adverse effect/s, the availability of such data may help clinicians tailor treatment options. Although some reports have suggested monitoring blood plasma concentrations of OLZ as a predictor of weight gain, 30 the calculated PPV and NPV in the present study are more clinically feasible measures because the modest PPV is greater than the proportion of patients who experienced SWG (29.1% vs 20.6%) and the NPV is greater than the proportion of patients who did not experience SWG (83.7% vs 79.4%). Monitoring weight and educating patients is less invasive than blood sampling, provides educational and health benefits to more patients, and follows National Institutes of Health weight management recommendations to the general public.…”
Section: Discussionmentioning
confidence: 79%
“…For patients identified as most likely to experience adverse effect/s, the availability of such data may help clinicians tailor treatment options. Although some reports have suggested monitoring blood plasma concentrations of OLZ as a predictor of weight gain, 30 the calculated PPV and NPV in the present study are more clinically feasible measures because the modest PPV is greater than the proportion of patients who experienced SWG (29.1% vs 20.6%) and the NPV is greater than the proportion of patients who did not experience SWG (83.7% vs 79.4%). Monitoring weight and educating patients is less invasive than blood sampling, provides educational and health benefits to more patients, and follows National Institutes of Health weight management recommendations to the general public.…”
Section: Discussionmentioning
confidence: 79%
“…Moreover, the doses compared may not be the doses clinicians are most concerned about when treating patients on high doses, which commonly exceed 20 mg daily among persistently mentally ill patients [60]. When considering surrogate markers, one study has shown that the serum concentration of clozapine and the ratio of olanzapine to N-desmethylolanzapine, one of its metabolites, were correlated with insulin, C-peptide and triglycerides [61].…”
Section: Biological Gradientmentioning
confidence: 99%
“…1,2 Excess weight gain is associated not only with social stigma and a lower quality of life, it also has a great impact on somatic comorbidity. 3 Thus, the search for an effective method to counteract weight gain would be beneficial.…”
mentioning
confidence: 99%